Efficient Production of Osteopontin-Encapsulating Exosome by LPS Stimulated THP-1 Macrophages - Bai, Gaowa; Matsuba, Takashi; Niki, Toshiro; Hattori, Toshio (Recent Research Advances in Biology Vol. 11, 2021)
Osteopontin (OPN) mediates bone remodeling and tissue debridement. The OPN protein is cleaved, but it is unclear how full-length (FL)-OPN or its cleaved form perform their biological activities in target cells. We, therefore, performed the molecular characterization of OPN in exosomes (Exo). The Exo were isolated from lipopolysaccharide (LPS)-stimulated phorbol 12-myristate 13-acetate (PMA)-differentiated THP-1 macrophages. The Exo were also isolated from PMA-differentiated THP-1 macrophages. The Exo were identified using the qNano multiple analyzer (diameter 59–315 nm) and western blotting with a CD9 antibody. LPS-stimulated cells produced more particles than non-stimulated cells. The presence of the FL or the cleaved form of OPN was confirmed using western blot analysis. A mixture of FL and cleaved OPN was also measured using an ELISA system (Ud-OPN) and their presence in the Exo was confirmed. Ud/FL ratios became low after LPS stimulation, indicating the enhanced encapsulation of FL-OPN in the Exo by LPS. These findings suggest that LPS stimulation of human macrophages facilitates the synthesis of FL-OPN, which is cleaved in cells or the Exo after release. These findings indicate that Exo is a suitable vehicle to transfer OPN to the target cells. It is necessary to investigate its role in COVID-19 infection.